BIOSORPTION OF AMOXICILLIN FROM CONTAMINATED WATER ONTO PALM BARK BIOMASS: Life Sciences-Antibiotics Removal - DAVOUD BALARAK; ALI JOGHATAYI; FERDOS KORD MOSTAFAPOUR; HOSSEIN AZARPIRA (International Journal of Life Science and Pharma Research, 2022)
The adsorption of amoxicillin (AMX) onto palm bark from aqueous solutions was studied in a batch adsorption system. Factors influencing AMX adsorption such as initial AMX concentration (10–100 mg/L), contact time (10–180 min), and adsorbent dosage (0.5–5 g/L) were investigated. The maximum removal efficiency of AMX was 98.1% under optimum conditions of adsorbent dose 3 g/L, contact time of 90 min and temperature 25 0C and initial AMX concentration 10 mg/L. Adsorption isotherms models including Langmuir, Freundlich and Temkin were tested. It was inferred that the Langmuir models (with very high R2 values) were most suited to describe the sorption of AMX in aqueous solutions and the monolayer adsorption capacity of AMX was found to be 35.92 mg/g.